The Effects of Harmonic Components on Transformer Rating - Masri, Syafrudin; Harjono, Purwo (ELKHA : Jurnal Teknik Elektro, 2009)
Abstract This paper presents the effects cause by non-linear load which containing harmonic components on the rating of power transformer. The usage of non-linear load will simply relates to the increased of transformer temperature. The abnormal heat rise in the transformer will lead to deterioration and increase the potential reduction of its lifetime. Due to the increased of heat, load supplied by the transformer should be reduced or to supply the same load, the power transformer should be changed to a higher rating to sustain the heat rise and these phenomenon known as de-rating. The selection of higher rating transformer is based on load THD where transformer kVA is a function of THD with the assumption that THD, transformers temperature and rating are stay linearity. Keywords Harmonic components, transformer rating, de-rating, linearity